Operational Control of an Unmanned Helicopter to Ensure an Emergency Safe Landing on an Unequipped Pad - Evdokimenkov, V. N.; Gogolev, A. A.; Ermakov, P. G. (Journal of computer & systems sciences international, 2024)
The problem of ensuring an emergency landing of an unmanned helicopter (UH) flying in a certain area of the target application is considered. A two-stage algorithm for searching for a suitable landing pad, taking into account the set of requirements, is proposed. At the first stage, using a digital elevation map (DEM) placed onboard a UH, a route around areas potentially suitable for landing in terms of the surface topography is calculated. The route is formed by sequentially solving static optimization problems in order to minimize the average losses that occur when a UH flies from one an landing pad to another. At the second stage, which is implemented directly during the movement of a UH along the calculated route, the final selection of the landing site is made based on the processing of ground penetrating radar data to confirm the soil density requirements at the landing site. A neural network classifier based on a two-layer perceptron is used to assess the suitability of the landing site in terms of the soil density requirement. An example that illustrates the operation of the proposed algorithm both under the conditions of a computational experiment and during a series of flight experiments is considered.